The question of the prohibition of prostitution in Europe: A comparative overview of the Nordic and the German- Dutch model and the inconsistencies of the Greek Legislation - Πολυχρονίου (Ariadni Polichroniou), Αριάδνη (Bioethica, 2019)
This article attempts to analyze and compare the two most influential systems that regulate prostitution in Europe: the Nordic model that is based on the total prohibition of prostitution and on the penalization of the purchase of sexual services and the German-Dutch model that introduces the normalization of prostitution via the legalization of the activity in question and the imposition of State controls and regulations. Furthermore, the article will focus on the policy of the European Union as well as on the Greek legislation regarding the confrontation of the phenomenon of prostitution. As far as the latter is concerned, the inconsistencies of the current legal framework and its applicability problems will be highlighted and the first efforts aiming at an alternative regulation of prostitution will be described.